Common Scab of Potato - Sparks, Adam (My University, 2008)
Common scab of potato is caused by a common soil-inhabiting bacterium, Streptomyces scabies. This is a guide to controlling the bacterium.
EP148_2008-05
Keywords: EP148; Crops; Lawn and Garden; Health and Safety; EP